The COVID-19 pandemic and its impacts on diet quality and food prices in sub-Saharan Africa - Ismail, Abbas; Madzorera, Isabel; Apraku, Edward A.; Tinkasimile, Amani; Dasmane, Dielbeogo; Zabré, Pascal; Ourohire, Millogo; Assefa, Nega; Chukwu, Angela; Workneh, Firehiwot; Mapendo, Frank; Lankoande, Bruno; et al. (PLOS ONE, 2023)
Background Sub-Saharan Africa faces prolonged COVID-19 related impacts on economic activity, livelihoods and nutrition, with recovery slowed down by lagging vaccination progress. Objective This study investigated the economic impacts of COVID-19 on food prices, consumption and dietary quality in Burkina Faso, Ethiopia, Ghana, Nigeria, and Tanzania. Methods We conducted a repeated cross-sectional study using a mobile platform to collect data from July-December, 2021 (round 2). We assessed participants’ dietary intake of 20 food groups over the previous seven days and computed the primary outcome, the Prime Diet Quality Score (PDQS), and Dietary Diversity Score (DDS), with higher scores indicating better quality diets. We used generalized estimating equation (GEE) linear regression models to assess factors associated with diet quality during COVID-19. Results Most of the respondents were male and the mean age was 42.4 (±12.5) years. Mean PDQS (±SD) was low at 19.4(±3.8), out of a maximum score of 40 in this study. Respondents (80%) reported higher than expected prices for all food groups. Secondary education or higher (estimate: 0.73, 95% CI: 0.32, 1.15), medium wealth status (estimate: 0.48, 95% CI: 0.14, 0.81), and older age were associated with higher PDQS. Farmers and casual laborers (estimate: -0.60, 95% CI: -1.11, -0.09), lower crop production (estimate: -0.87, 95% CI: -1.28, -0.46) and not engaged in farming (estimate: -1.38, 95% CI: -1.74, -1.02) were associated with lower PDQS. Conclusion Higher food prices and lower diet quality persisted during the COVID-19 pandemic. Economic and social vulnerability and reliance on markets (and lower agriculture production) were negatively associated with diet quality. Although recovery was evident, consumption of healthy diets remained low. Systematic efforts to address the underlying causes of poor diet quality through transforming food system value chains, and mitigation measures, including social protection programs and national policies are critical.
Gesehen am 07.12.2023